Pengaruh Media Visual dan Motivasi Belajar Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Pendidikan Kewarganegaraan Kelas XI PMIA SMA Negeri 3 Pematang Siantar - Milani Permatasari Siahaan; Sepriandison Saragih; Melvin Simanjuntak (Badan Penerbit STIEPARI Press, 2022)
This research aims to find out whether or not The Influence Of Visual Media And Student Learning Motivation On Student Achievement. To obtain data on task-giving skills and how to learn, researchers use questionnaires as data collection tools and the ones used are closed questionnaires arranged in a structured The quality of research instruments for questionnaires is assessed through vadilitas and rehabilitation tests. This research do the class XI SMA Negeri 3 Pematang Siantar. using a match test or chi quadratic test and it turns out that the two variables are normally distribution. The hypothesis testing by calculating the linear regression equation i.e. Y over X1 is = 81,93 + 0.09X1 means that between the linear variableS X1 with Y and Y over X2 is = 90.15 + 0.09X2 This means that between the variables X2 linear with Y and Y above X1 and X2 is = 1,2 + 0.61X1 + 0.68X2 means that between variables X1 and X 2 linear with Y.